A study on clinical and laboratory profiles of hemorrhagic and ischemic strokes in an Eastern Indian teaching Hospital - Kabi, Shobhitendu; Padhy, Rajesh; Panda, Baikuntha N.; Rath, Siba N.; Padhy, Rabindra N. (International Journal of Research in Medical Sciences, 2017)
Background: Stroke is a frequent cause of death and disability. This study was carried out to establish the pattern of various types of cerebrovascular accident (CVA) and comparison between hemorrhagic and ischemic stroke in Eastern India. Methods: This is a retrospective study of sample size 367 CVA patients; among them, 218 were ischemic and 149 were hemorrhagic admitted to Department of General medicine and Neurology of the hospital. Results: Of the total 367 patients, there were 149 as hemorrhagic stroke patients and 218 patients as ischemic stroke patients. Ratio of hemorrhagic to ischemic stroke was 40.6: 59.4. Among patients in hemorrhagic patients male to female ratio was 1.6:1 and in ischemic stroke patients male to female ratio was 1.27:1. It was recorded that prevalence of ischemic stroke was higher than hemorrhagic type. Conclusions: The CVA was associated with blood pressure, cholesterol and use of tobacco as the common risk factor for ischemic stroke. It was recorded that ischemic stroke patients had reported frequently than hemorrhagic patients.